Nursing cooperation in transurethral resection of prostate under comprehensive body temperature control (综合控温干预下经尿道前列腺电切术的护理配合) - YANG Xue (杨雪); SHEN Jianhui (沈剑辉) (中西医结合护理)
This paper summarized the nursing cooperation in transurethral resection of prostate under comprehensive body temperature control. The clinical data of 80 patients who received transurethral resection of prostate were retrospectively analyzed. The comprehensive body temperature control strategy was carried, including adequate preoperative preparation and targeted nursing interventions during operation. There was no intraoperative hypothermia or massive hemorrhage reported, and patient’s blood pressure was stable during the surgery. Based on perioperative nursing cooperation, adopting comprehensive body temperature control showed a positive effect on reducing the risk of intraoperative hypothermia and postoperative complications. (总结综合控温干预下经尿道前列腺电切术的护理配合。回顾医院2021年12月—2022年12月收治的经尿道前列腺电切术治疗的80例患者的临床资料。采取综合控温措施实施干预, 包括充分的术前准备, 术中针对性护理措施。患者术中无低体温发生, 无大出血, 血压平稳, 手术顺利进行, 术后无相关并发症。对经尿道前列腺电切术患者采取综合控温干预措施, 同时完善围手术期护理, 对降低术中低体温和术后相关并发症发生风险具有积极意义。)